The Obligatory Electronic Invoicing and Reporting as A Digital Ecosystem - Ranchev, Georgi (Research Papers, 2021)
Subject to the present article are the VAT gap as well as the measures undertaken by some of the European Union member states including the introduction apart from public tenders of obligatory electronic invoicing and reporting as a separate digital ecosystem. The results of a recent survey on the expected effects of the digital transformation processes and obligatory electronic invoicing on budget revenues and the business are also provided.
Keywords: Digital transformation; Electronic invoicing